A low complexity precoding based on weighted two diagonal iteration in massive MIMO system - Haiyan CAO; Dong ZHOU; Fangmin XU; Xin FANG; Xiumin WANG (Dianxin kexue)
In massive MIMO systems,with the increase of the number of users and antennas,the complexity of the downlink zero forcing (ZF) precoding increases due to the existence of large matrix inversion.In order to reduce the complexity,an improved weighted two diagonal iteration precoding algorithm based on the Jacobi iterative algorithm was proposed.The low-two diagonal matrix was taken as iterative matrix,and the iterative results were weighed addition with the last results to accelerate the convergence speed of the iteration.According to the diagonally dominant characteristic of channel matrix in massive MIMO systems,the first term of the Neumann approximation of matrix inversion was used as the initial value of the iteration to accelerate the iteration further.Compared with the traditional ZF precoding,the proposed scheme can reduce the complexity with an order of magnitude and ensure the performance of the precoding scheme.